Highly Efficient Li−Air Battery Using Linear Porosity Air Electrodes. Issue 9 (29th April 2020) - Li, Jie; Yan, Fangzheng; Su, Zipeng; Zhang, Tianyu; Zhang, Xiaochen; Sun, Hong
Abstract : An advanced transient state model was developed based on the dynamic behavior of the porous air electrode of non-aqueous Li-air battery, which was determined by a numerical solution of the combined continuity, transport, and kinetics equations. The effects of linear porosity in air electrode on the detail performance such as the distribution of the oxygen concentration, Li2 O2 volume fraction, porosity, and oxygen diffusion coefficient of non-aqueous Li-air battery during the discharge were investigated. The results revealed that the employing linear porosity air electrode leaded to the higher specific capacity, the uniform porosity and the preferable oxygen diffusion coefficient of Li-air battery caused by the high-efficiency utilization of porous air electrode and sufficient oxygen transfer. The discharge current density had significant effects on the property of Li-air battery based on linear porosity air electrode due to the great increasing of ohm polarization and serious air electrode passivation. The porosity became uniformly with the reaction, which indicated utilization rate of air electrode near membrane side was significantly improved due to the large initial oxygen concentration difference. The detailed results provided a deeper understanding of producing more efficient Li-air batteries as potential power sources to expand the range of electric vehicles.